TINDAKAN USNS IMPECCABLE DALAM MELAKUKAN KEGIATAN DI 75 MIL SELATAN PULAU HAINAN - Maya Ajeng Nur’Aini; Anto Ismu Budianto (Fakultas Hukum Universitas Trisakti, 2021)
Marine scientific research collect all types of data carried out at sea such as oceanography, marine biology, and hydrography. Marine scientific research is carried out with the consent of the coastal state and is carried out for peaceful purposes. The research’s issues are whether the actions of the USNS ship conducting marine scientific research in 75 miles south of China's Hainan Island violated the 1982 KHL and whether the USNS ship's actions could be proven as military activity, namely reconnaissance at the Yulin Sea Base based on the 1982 KHL. This research conducted in normative methods and using data obtain through literature studies. The conclusion of this research is that the USNS Impeccable in its activities violated the 1982 KHL. The USNS Impeccable carried out its activities in 75 miles of China's Hainan Island which is an EEZ claimed by China. The USNS Impeccable ship did not give prior notification of its activities as stipulated in Article 58 of the 1982 KHL and its activities could be proven as military activities because it threatened China's sovereignty in its activities which also indicated reconnaissance of the Yulin Sea Base which violated article 301 of the 1982 KHL.